GAMBARAN EVAKUASI DIRI PADA SIMULASI BENCANA GEMPA BUMI DI PANTI ASUHAN RUMAH PENGHARAPAN BARU - Sirumani Gea, Untung Sudharmono (Jurnal Medika Hutama, 2025)
Indonesia is a disaster-prone country, including West Java, which is traversed by the Lembang Fault. Rumah Pengharapan Baru Orphanage is located in an earthquake-prone area, making disaster simulation and education crucial to improve children's preparedness. This study aims to find out the picture of the preparedness capacity of children at the Rumah Pengharapan Baru Orphanage in carrying out self-evacuation during an earthquake disaster simulation. This research used a descriptive quantitative method with purposive sampling. Forty children participated as research subjects, and their evacuation behavior was observed through video recordings of the simulation. The observed indicators were calm behavior, head protection, use of footwear, and gathering at the assembly point. The results showed that elementary students had an average evacuation behavior score of 91%, junior high school students 86%, and senior high school students 82%. The total evacuation time to the assembly point was 3 minutes and 18 seconds. Some children did not wear footwear or failed to protect their heads during evacuation. In conclusion, most children showed good preparedness in self-evacuation, although there are areas needing improvement. It is recommended that children prepare footwear in their dorm rooms, and that the orphanage holds regular disaster simulation programs to enhance preparedness.